Imaginary and real visualization of Kazan as the Russian East by French travelers (1839) - A.A. Kouznetsov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
The paper is devoted to the perception of Kazan and Kazan province as the Russian East by French travelers. Astolphe de Custine and André Durand traveled to Russia in 1839. Custine, following the results of his visit to Russia, wrote the book “Russia in 1839” (La Russie en 1839). Duran captured the images of Russia in lithographs. The relevance of the research is due to the widespread opinion of Custine’s work as the beginning of the collective dislike of the West for Russia. The scientific importance is determined by the source study of the correlation of texts and artistic images on one topic. The study was performed to find out the impressions that Custine could get from Kazan as the oriental locus of the Russian Empire. As a means of verifying the alternative history hypothesis, nine Durand’s lithographs of Kazan were used. The results of the study include: the evolution of Custine’s ideas about Russia from the embodiment of the East to the phenomenon on the border of Asia and Europe; Custine’s emotional and intellectual discomfort as the cause of the hypercriticism of his book; Custine’s refusal to visit Kazan as a missed opportunity to see the eastern nature of Russia; Durand fixing the Islamic, Tatar realities in Kazan and Kazan province. The results obtained are important for the formulation and solution of the following problems: source study of synchronous and monocultural representations of textual and graphic visualization; research on Custine’s book “Russia in 1839” in connection with Durand’s lithographs; study of Kazan local history and everyday life.